From gene to biorefinery: microbial β-etherases as promising biocatalysts for lignin valorization - Picart, Pere; Domínguez de María, Pablo; Schallmey, Anett (Frontiers in Microbiology, 2015)
The set-up of biorefineries for the valorization of lignocellulosic biomass will be core in the future to reach sustainability targets. In this area, biomass-degrading enzymes are attracting significant research interest for their potential in the production of chemicals and biofuels from renewable feedstock. Gluthatione-dependent β-etherases are emerging enzymes for the biocatalytic depolymerization of lignin, a heterogeneous aromatic polymer abundant in Nature. They selectively catalyze the reductive cleavage of β-O-4 aryl-ether bonds which account for 45-60% of linkages present in lignin. Hence, application of β-etherases in lignin depolymerization would enable a specific lignin breakdown, selectively yielding (valuable) low-molecular-mass aromatics. Albeit β-etherases have been biochemically known for decades, only very recently novel β-etherases have been identified and thoroughly characterized for lignin valorization, expanding the enzyme toolbox for efficient β-O-4 aryl-ether bond cleavage. Given their emerging importance and potential, this mini-review discusses recent developments in the field of β-etherase biocatalysis covering all aspects from enzyme identification to biocatalytic applications with real lignin samples.